1995
DOI: 10.1002/ajmg.1320600111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic threshold hypothesis of neocortical spike‐and‐wave discharges in the rat: An animal model of petit mal epilepsy

Abstract: Neocortical high-voltage spike-and-wave discharges (HVS) in the rat are an animal model of petit mal epilepsy. Genetic analysis of total duration of HVS (s/12 hr) in reciprocal F1 and F2 hybrids of F344 and BN rats indicated that the phenotypic variability of HVS cannot be explained by a simple, monogenic Mendelian model. Biometrical analysis suggested the presence of additive, dominance, and sex-linked-epistatic effects, buffering maternal influence, and heterosis. High correlation was observed between averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Similar to previous reports [4244], SWDs appeared to vary with the environment of animals. In previous studies environmental influences did not include housing during early life (although development has been suggested to play a role; [44]).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous reports [4244], SWDs appeared to vary with the environment of animals. In previous studies environmental influences did not include housing during early life (although development has been suggested to play a role; [44]).…”
Section: Resultssupporting
confidence: 91%
“…In previous studies environmental influences did not include housing during early life (although development has been suggested to play a role; [44]). Therefore, it is notable that we report here a potential facilitatory effect of housing, especially early in life, on SWDs.…”
Section: Resultsmentioning
confidence: 99%
“…HVS, large amplitude sharp spindles, mimic SWDs, although not all included HVS would unambiguously classify as SWDs, since the spikes of the HVS might be less sharp and the waves were sometimes missing. 16 6-8 months old rats (Fischer 344 and Brown Norway strains) were used to develop and train the system, as well as their F1 and F2 descendents, and back-crosses with the parental strains for its evaluation and subsequent quantitative genetic analyses of the HVS (Vadász et al, 1995). An artificial neural network was used, which should be first properly trained before its generated the desired output of the test data set.…”
Section: Detection Of Swds: Off Line Methodsmentioning
confidence: 99%
“…for genetic analyses of absence epilepsy Vadász et al, 1995;Gauguier et al, 2004). These long lasting recordings are also necessary for the study of long term drug effects and epileptogenesis , for chronic drug studies (D'Amore et al, 2014), for the study of circadian rhythms of SWDs and the consequences of their shifts (Smyk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, thalamocortical μ rhythm is sex and strain dependent in both rats and mice (Peeters et al, 1992; Marescaux et al, 1992; Vadász et al, 1995; Noebels 2003). A study of REM sleep in numerous strains of mice indicated the presence of a gene with a major effect on theta frequency, which could explain more than 80% of the total variability among strains (Franken et al, 1998).…”
Section: Brain Rhythms Are Robust and Heritable Phenotypesmentioning
confidence: 99%